A National Adaptation Programme of Action: Ethiopia's responses to climate change. (March 2016) - Golrokhian, Arman; Browne, Katherine; Hardin, Rebecca; Agrawal, Arun; Askew, Kelly; Beny, Laura; Larroquette, Benjamin; Morse, Benjamin
Abstract: This innovative sustainability case on Ethiopia's National Adaptation Programme of Action was created through collaboration among professionals, scholars, students and media design professionals under the auspices of the Michigan Sustainability Case (MSC) initiative. It comprises a terse narrative about a decision maker, multimedia sources including a podcast that link to and enrich the text, and an engaged learning exercise that walks users through the potential and constraints of emerging cost–benefit analysis methods for climate adaptation planning. It challenges learners to address the emerging impacts of climate change by systematically analyzing the challenges faced by Ethiopia's central government in allocating limited financial, technical and administrative resources to mitigate these impacts on its most vulnerable communities. The case not only introduces audiences to climate change risks and vulnerabilities in Ethiopia, but also interweaves those contextual factors with broader technical information, to strengthen understanding of the specific governance challenge at hand. The case thus demonstrates MSC's pedagogical commitment to making ecological, economic, cultural and political context clearer in the development of effective environmental policies. Likewise, the MSC approach deliberately demonstrates to students the challenges of decision-making with imperfect information.